Aplikasi M. Learning Pendidikan Seksualitas untuk Orangtua Anak Autis di Komunitas Sekolah Cemara Surabaya - Friskadia Putri Ekinasmara; Lena N. Panjaitan (Universitas Muhammadiyah Jember, 2021)
Autism is a neurological disorder that affects children's social skills, communication and behaviour. The broad and severe impact raises its challenges in providing sexuality education for autistic children. The results of the needs assessment show that not all parents understand that children with autism continue to experience sexual development like children with normal development. In addition, parents also really need information about how to provide sexuality education to autistic children. Based on the results of the assessment, the researchers developed an M. Learning application design with smartphone media to increase parents' knowledge of sexuality education for autistic children. M. Learning was chosen because it can contain information on child sexuality education while still supporting the mobility of parents so that it can be accessed anytime and anywhere. The design of the M. Learning application was compiled based on various references from previous research, sexuality education booklets and books as well as discussions with educational psychologists. The coding of applications on smartphone media is carried out by information technology experts so that the information that has been compiled can be accessed easily.